Archaeological stratigraphy (Scottish Historical and Archaeological Internet Reports, 2001)
The results of the excavations are described in terms of historic periods reflecting the building, occupation and abandonment of structures towards the east end of the south range, from the later 12th century to the present time. In total, five periods of building, occupation and abandonment of the structures at the south-east corner of the cloister were identified, and the archaeological account is presented in these terms. In addition, a period of activity spanning Periods IV and V was identified from the deposits within the great drain, and overlying it. The periods are defined as follows: period I '“ c 1170-1230; period II '“ c 1230-1320; period III '“ c 1320-1450; period IV '“ c 1450-1520; period V '“ c 1520-1600; occupation over periods IV-V '“ the midden and the great drain fills.